2019
DOI: 10.1021/acs.inorgchem.8b03475
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Counterion on the Synthesis of Cyclic Carbonates Catalyzed by Bifunctional Aluminum Complexes

Abstract: New bifunctional aluminum complexes have been prepared with the aim of studying the effect of a counterion on the synthesis of cyclic carbonates from epoxides and carbon dioxide (CO2). Neutral ligand 1 was used as a precursor to obtain four novel mesylate, chloride, bromide, and iodide zwitterionic NNO ligands (2–5). The reaction of these ligands with 1 or 2 equiv of AlR3 (R = Me, Et) allowed the synthesis of mono- and bimetallic bifunctional aluminum complexes [AlR2(κ2-mbpzappe)]­X [X = Cl, R = Me (6), Et (7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 70 publications
1
22
1
Order By: Relevance
“…Cyclic carbonates are characterized by a range of applications, for instance: monomers for polymerization, substrates in organic synthesis, green solvents, or electrolytes for lithium‐ion batteries [48, 49] . From the above reasons, a number of research groups have focused their attention on the preparation of efficient catalytic systems for cyclic carbonate synthesis including metal complexes with imine, [50–54] aminophenolate, [55, 56] porphyrin, [57, 58] or other ligands [59–62] . Also, an organocatalytic approach has actively been investigated [63–65] …”
Section: Introductionmentioning
confidence: 99%
“…Cyclic carbonates are characterized by a range of applications, for instance: monomers for polymerization, substrates in organic synthesis, green solvents, or electrolytes for lithium‐ion batteries [48, 49] . From the above reasons, a number of research groups have focused their attention on the preparation of efficient catalytic systems for cyclic carbonate synthesis including metal complexes with imine, [50–54] aminophenolate, [55, 56] porphyrin, [57, 58] or other ligands [59–62] . Also, an organocatalytic approach has actively been investigated [63–65] …”
Section: Introductionmentioning
confidence: 99%
“…From these experiments, the hypothesised trend of thermally unstable anilinium salts leading to more efficient methylation did not hold. Indeed, three of the most thermally unstable anilinium iodides 2a-4a and 15a -all carrying strong electron-withdrawing aryl substituents -led to measurable quantities of SNAr products (18)(19)(20)(21) and poor yields of desired methylation products. Indeed, analysis of thermal degradation versus O-methylation efficiency within the anilinium salt library revealed that only those unstable salts bearing no resonance withdrawing aryl substituents served as efficient methylating reagents.…”
Section: Applications Of Mechanistic Analysis In Methylation Chemistriesmentioning
confidence: 99%
“…Applications and divergent reactivity of trimethylanilinium salts. N,N,N-trimethylanilinium salts have found wide-ranging applications in synthesis, spanning phase-transfer catalysis, 1 supramolecular ion-pairing catalysis, 2,3 host-guest binding studies, 4 O-methylation, 5 O-arylation, 6 heteroatom arylations, 7 C-H methylation, 8 C-arylation, [9][10][11] fluorine radiolabeling, [12][13][14][15] organometallic ligand design, [16][17][18][19][20][21] antimicrobial polymer design, 22 and a range of metal-catalysed cross-coupling methodologies. [23][24][25][26][27][28][29] The dichotomy of arylation versus methylation reactivity, while important for optimising the above-listed applications, is rarely studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of such systems active for terminal, internal and trisubstituted epoxides have been reported so far. [6] In view of more sustainable protocols, special emphasis has been devoted to non-endangered metal catalysts [7] such as salts and complexes of Fe, Al, Co and Zn, [8][9][10][11] and, even more interesting, some of these systems have proved efficient in continuous-flow (CF) mode, i. e. under highly reliable conditions for process optimization, intensification and upscaling. [12] One of the first CF-examples described a Co II -salen complex immobilized on MCM-41 silica gel: at T = 110°C, p(CO 2 ) = 125 bar and F = 10-20 mL • h À 1 , in the presence of tetrabutylammonium bromide (TBAB) as a co-catalyst, ethylene oxide (EO) was converted up to 86 % into ethylene carbonate (EC) with > 99 % selectivity.…”
Section: Introductionmentioning
confidence: 99%